FORMATION OF THE INNOVATION POTENTIAL OF COMPANIES IN THE CONDITIONS OF DIGITALIZATION - FYLIUK, Halyna; SHICHAO, Chang (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The relevance of the problem of innovative potential formation of companies in Ukraine is determined. The issues of interdependence of the processes of digital transformation and innovative potential formation of companies in modern conditions are analyzed. The essence of the concept "innovative potential of a company" has been clarified. A model of functional and structural decomposition of the company’s innovative potential formation is developed as a basis for a deep systematisation and study of the innovative processes taking place in the company. Dynamics of the development of innovation activity of Ukrainian companies are analyzed. It is investigated that digitalization processes at the macro level are being implemented more dynamically than at the micro level in Ukraine. Trends to decrease the innovation activity of domestic industrial enterprises over the past 20 years have been identified. It is proved that our country is taking some steps to create a favourable ecosystem for the development of digital technologies and the formation of innovative potential by business. The article reveals the reasons that reduce the innovative activity of Ukrainian companies, slow down the processes of digital transformation, and complicate the process of innovative potential formation: lack of financial resources, low level of national scientific and technical potential, regulatory imperfection for intellectual property of innovators, low level of innovation culture in the country, prevalence of short-term thinking over long-term thinking due to high turbulence in the external environment, excessive bureaucratisation of innovation administrative procedures, a growing shortage of qualified personnel, deficiencies in effective demand for innovation in the domestic market, etc. A research proposal includes a creation of favourable conditions for intensifying the processes of digitalization of companies’ activities and developing their innovation potential.